2019
DOI: 10.3390/su12010273
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Caused by Increased Use of E-Powered Personal Mobility Vehicles in European Cities

Abstract: Increased use of e-powered personal mobility vehicles is usually considered to be a positive change, while it is generally agreed that Personal Mobility Vehicles (PMVs) effectively and efficiently reduce the negative environmental impacts of transport and improve quality of life. There has been great technological progress made by all sectors in the field of personal mobility during the last decade. The use of PMVs for micro-mobility have been welcomed by the market, consumers, and governments and thus they ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 97 publications
(68 citation statements)
references
References 48 publications
1
34
0
Order By: Relevance
“…The results state that there is a heterogeneity of gender in using PMV among participants that is consistent with the former studies [37][38][39]. Gender plays an important role in the preferences regarding PMV use.…”
Section: Discussionsupporting
confidence: 89%
“…The results state that there is a heterogeneity of gender in using PMV among participants that is consistent with the former studies [37][38][39]. Gender plays an important role in the preferences regarding PMV use.…”
Section: Discussionsupporting
confidence: 89%
“…James et al [312] analyzed initial situations of illegal parking and walkways blocking and found that 16% of scooters were illegally parked and 6% blocking walkways. An overview of challenges caused by micro-mobility is given in [313]. To improve safety, a dedicated policy should be adopted to regulate riders' behavior.…”
Section: Shared Micro-mobilitymentioning
confidence: 99%
“…One of the long-term objectives of this research is to provide a dynamic (per unit time) snapshot model of downtown parking for designing parking informatics systems. Unlike the ones proposed in the literature, there is a need for parking and delivery information systems for both commuters and delivery van drivers (Amer & Chow, 2017;Zagorskas & Burinskienė, 2020). For this reason, the ICT systems should be applied in optimising old town mobility and especially parking.…”
Section: Literature Reviewmentioning
confidence: 99%